Effectiveness and safety of atosiban versus conventional treatment in the management of preterm labor - Yan Yu; Zhi Yang; Liya Wu; Yuanfang Zhu; Fang Guo (Elsevier, 2020)
Objective: To compare the efficacy of atosiban with conventional treatment of the threatened preterm labor. Materials and methods: All the data of pregnant women with threatened preterm labor from January 1 to December 31, 2017, who received atosiban were collected. Pregnant women with conventional treatment (including β-agonists, indomethacin, magnesium sulphate and calcium channel blockers, alone or in combination) were used as control. Results: The proportion of women not requiring an alternative tocolytic treatment within 48 h and remaining undelivered was significantly higher in atosiban treatment group (89.3%; n = 25/28) compared with conventional treatment (24.2%; n = 8/33) (P < 0.0001). For therapy efficacy, there was also no significant difference between atosiban groups and conventional treatment groups in the low gestational ages. However, for the high gestational ages, atosiban treatment group showed higher efficacy (84%; n = 21/25 vs. 37.5%; n = 3/8) (P < 0.05). Moreover, a significantly higher proportion of women in the atosiban treated group (89.3%; n = 25/28) was observed compared with the conventional treatment groups (51.5%; n = 17/33) who did not receive an alternative tocolytic within 48 h (P < 0.01). Maternal and fetal safety was significantly superior with atosiban treatment. Conclusions: Our results support that atosiban would represent an advance over current tocolytic therapy especially for the high gestational ages.